Outsourcing sustainability in US expeditionary operations: the contribution of private military and security industry in Phase IV Operations in Iraq 2003-2011 - Jonasova, Jana (2017)
This thesis examines the contribution of the Private Military and Security Industry (PMSI), as an element of the United States (US) total force, to the US military capability in pursuing Phase IV Operations in Iraq from 2003 until 2011. In order to do so, the study proposes a typology of five types of contribution categories which define the link between the ends demanded by the US government (strategic goals) and the use of the PMSI as a tool to help achieve them. By incorporating a model from the operations management field, the Hayes and Wheelwright's Four-Stage model, this thesis identifies the categories of Assistant, Implementer, Crucial Supporter, Driver, and Spoiler as distinct forms of engagement, constituting a framework for the assessment of the nature of the relationship between the contractors’ activities and the strategic goals they sought to help achieve. Applied to the case studies of armed private security services and base support services, this framework reveals that contractors became the Crucial Supporter of the US military efforts in Phase IV Operations in Iraq. In the aftermath of the ill-planned regime-change, followed by unforeseen operational circumstances on the ground, and constrained by the US domestic policy reservations towards prolonged nation-building efforts, the US government found both armed security contractors and base support contractors to be a critical asset of the US military strategy on the ground. Through their constructive contribution towards the size of the deployable force, the available timeframe, the objectives and the strategic goal of these operations, they became a key partner of the US military efforts in Iraq. Utilising a descriptive and exploratory approach, and relying on a range of sources, including official documents, semistructured interviews and publicly available video testimonies of US veterans from Iraq, this thesis highlights the PMSI’s strategic value in a complex expeditionary operation while providing a detailed insight in the complexity of modern warfare.